Increased expression of vascular endothelial growth factor and its receptor in enlarging brain arteriovenous malformations – a case report. (January 2014) - Kashiwazaki, Daina; Kobayashi, Rina; Houkin, Kiyohiro; Kuroda, Satoshi
Abstract Case. A 24-year-old man with Spetzler–Martin (S–M) Grade III arteriovenous malformation (AVM). He was conservatively treated, but AVM significantly increased in size over 5 years, judged as Grade IV. Subsequently, he developed intracerebral hemorrhage. AVM was totally removed. Immunohistochemistry showed that the endothelial cells in the dura and nidus were positive for VEGF and VEGF-R.